1990
DOI: 10.1007/bf00032306
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate effects in leaf discs from spinach

Abstract: In this paper, we show the unique role of bicarbonate ion in stimulating the electron transfer of photosystem II (PS II) in formate-treated leaf discs from spinach. This is referred to as the "bicarbonate effect" and is independent of the role of CO2 in CO2 fixation. It is shown to have two sites of action: (1) the first, described here for the first time, stimulates the electron flow between the hydroxylamine donation site ("Z" or "D") and QA, the first plastoquinone electron acceptor and (2) the other accele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In the early 1970s the high-affinity pool had been ascribed to the donor side of PS-II [2,5,6] and a model including BC as a mediator for photosynthetic water oxidation had been suggested [5,6] which however was in contradiction with the results of isotopic experiments [7]. Wydrzynski and Govindjee [3] observed an accelerated rise of Chl fluorescence in BC-depleted chloroplasts which demonstrated that reoxidation of the first plastoquinone acceptor, Qa, by the plastoquinone pool has been impaired by the removal of BC which was supported by a number of data ( [8][9][10][11] and references therein). The non-heme Fe between QA and QB has been shown to play an essential role in BC binding [8].…”
Section: Introductionmentioning
confidence: 54%
See 3 more Smart Citations
“…In the early 1970s the high-affinity pool had been ascribed to the donor side of PS-II [2,5,6] and a model including BC as a mediator for photosynthetic water oxidation had been suggested [5,6] which however was in contradiction with the results of isotopic experiments [7]. Wydrzynski and Govindjee [3] observed an accelerated rise of Chl fluorescence in BC-depleted chloroplasts which demonstrated that reoxidation of the first plastoquinone acceptor, Qa, by the plastoquinone pool has been impaired by the removal of BC which was supported by a number of data ( [8][9][10][11] and references therein). The non-heme Fe between QA and QB has been shown to play an essential role in BC binding [8].…”
Section: Introductionmentioning
confidence: 54%
“…E-mail: Klimov@issp.serpukhov.su Abbreviations: BC, bicarbonate; DCMU, 3-(3,4-dichlorphenyl)-l, 1-dimethylurea; DCPIE 2,6-dichlorophenol-indophenol; DPC, diphenylcarbazide; EDTA, ethylenediaminetetraacetic acid. effect) confirmed that BC evidently has two sites of action: the first accelerates the electron flow beyond Qa, and the other stimulates it between the secondary electron donor, Yz, and QA (the site between the primary electron acceptor, pheophytin, and QA was suggested for the latter case [10]). In this paper we present evidence for a BC requirement on the donor side of PS-II and for involvement of BC in reconstitution of the Mn cluster in Tris-washed PS-II membranes.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…The depletion of bicarbonate by its analogue formate results in a significant inhibition of the electron transfer on the acceptor side, i.e., from QA to the plastoquinone pool (see references in Blubaugh & Govindjee, 1988a;Govindjee & van Rensen, 1993). Studies have also suggested that bicarbonate may affect the donor side function of PSII (El-Shintinawy & Govindjee, 1990;Jursinic & Dennenberg, 1990;Stemler & Jursinic, 1993;Klimov et al, 1995;Wincencjusz et al, 1996).…”
mentioning
confidence: 99%